Harta dan Hak Milik dalam Islam: Pembagian Harta dan Akibat Hukumnya - Adri Adri; Ferdi Prayoga; Nurvina Hidayati; Aidil Alfin (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This research aims to examine Property and Property Rights in Islam: Property Distribution and Its Legal Consequences. This study uses a qualitative approach with a type of literature study (library research). This method aims for a Qualitative Study of Shirkah Its Implications on Sharia Banks and Islamic Financial Institutions, focusing on the application of application in daily life. The data in this study were collected through the search of relevant documents and secondary sources, such as Articles from national and international journals indexed by SINTA and Scopus, Property and Property Rights. The concept of property and property in Islam reflects the balance between individual freedom and the interests of society. Islam not only guarantees the right to property, but also sets limits so that wealth becomes a blessing and beneficial to all. By understanding this principle, Muslims are expected to be able to manage their property in a trustworthy and responsible manner. Islam recognizes and protects individual property as part of human rights. However, this right is not absolute, but is bound by moral values and Sharia law. Ownership must be used fairly, beneficially, and not cause social damage or inequality